Analisis Hasil Penelitian Pendidikan Islam Dengan Pendekatan Fisika - Sirajudin, Sirajudin; Mujib, Abdul; Abzar, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
The aim of this research is to analyze the results of Islamic education research using a physics approach, analyze the learning of Islamic values through physics modules, and analyze students' Islamic character through a physics approach based on the integration of Islamic science. This research uses library research. Referring to the research objectives, findings, and results of the discussion in this research, it is concluded that the results of the analysis of Islamic education using a physics approach show that, first, the relationship between physics lessons and Islam, and second, the integration between Islam and physics contained in the verses of the Koran in textbooks. containing Islamic nuances with verses from the Koran and local wisdom can train students' religious character; third, students' understanding of the relationship between physics and Islamic education; fourth, learning Islamic values through physics modules can make students interested in studying physics, which is related to science. Islam, and fifth, the application of physics learning based on science-Islamic integration can improve students' learning outcomes and Islamic character. It is hoped that this research can make a positive contribution to more effective Islamic education in the realm of science integration as a foundation for the development of Islamic education in a multidisciplinary context.